2002
DOI: 10.1177/1359104502007002006
|View full text |Cite
|
Sign up to set email alerts
|

Attention Deficit Hyperactivity Disorder is Associated with Attachment Insecurity

Abstract: The literature on attention deficit hyperactivity disorder (ADHD) and attachment is reviewed, and we describe an investigation of the relationship between attachment insecurity and ADHD. Nineteen boys, aged 5-10 years with DSM-IV diagnoses of ADHD were compared with 19 control children on three representational measures assessing internal working models of attachment and the self: the Separation Anxiety Test, the Self Interview, and a Family Drawing rated with an attachment-based scoring system. Consistent sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
1
8

Year Published

2003
2003
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(79 citation statements)
references
References 49 publications
5
65
1
8
Order By: Relevance
“…However, attachment theory holds that a secure and responsive early parent child relationship is an integral part of the development of effective selfregulation in the child and self-regulation is linked to impulse control, perseverance and inhibition, which make up important features of the nondeprivation-related I/O and ADHD phenotype. Most studies have focused on insecure attachment with parents, rather than disinhibition with strangers, and are mainly based on small clinical case studies (Stiefel 1997;Clarke et al 2002). Nevertheless, in combination with the striking pattern of disinhibited attachment observed in our sample and pattern of overlap noted by Kreppner et al (2001), these studies highlight this as an important area of investigation when considering the phenotypic characteristics of I/O in adolescence.…”
Section: Introductionsupporting
confidence: 33%
“…However, attachment theory holds that a secure and responsive early parent child relationship is an integral part of the development of effective selfregulation in the child and self-regulation is linked to impulse control, perseverance and inhibition, which make up important features of the nondeprivation-related I/O and ADHD phenotype. Most studies have focused on insecure attachment with parents, rather than disinhibition with strangers, and are mainly based on small clinical case studies (Stiefel 1997;Clarke et al 2002). Nevertheless, in combination with the striking pattern of disinhibited attachment observed in our sample and pattern of overlap noted by Kreppner et al (2001), these studies highlight this as an important area of investigation when considering the phenotypic characteristics of I/O in adolescence.…”
Section: Introductionsupporting
confidence: 33%
“…Turning to the attachment relationship and ADHD, Clarke et al (2002) pointed to the fact that children with ADHD and insecurely attached children share many features, such as poor self-regulation, disorganization, impulsiveness, and problematic social relations. Clarke and colleagues (2002) also reported empirical findings showing that children diagnosed with ADHD more often had insecure attachment representations compared to children in a comparison group.…”
Section: Poor Inhibition and The Attachment Relationship In Relation mentioning
confidence: 99%
“…Some researchers also suggested that the symptoms of attention-deficit hyperactivity disorders (ADHD) may develop in the context of an insecure attachment relationship (e.g. Clarke, Ungerer, Chahoud, Johnson, & Stiefel, 2002). More specifically, it has been advocated that the impairment in self-regulation seen in children with ADHD may have its roots in strained early caregiver-child interactions and disrupted primary attachments (Olson, 1996).…”
Section: Introductionmentioning
confidence: 96%